GPUfs: The Case for Operating System Services on GPUs. - SILBERSTEIN, MARK; FORD, BRYAN; WITCHEL, EMMETT (Communications of the ACM, 2014)
The article focuses on making core operating system abstractions available to graphics processing unit (GPU) code and the lessons learned in building GPUf file system layer. Topics discussed include how GPU have acquired increasingly general-purpose parallel processing capabilities, the traditional CPU-centric programming model and how GPUfs demonstrates the productivity and performance benefits of allowing GPU to guide data flow in a system. An overview of the GPU software/hardware model is given.